Sustainable Tourism, Integral Ecology and Training for an Educational Pact with the Territories - Patrizia Galeri (Pensa MultiMedia, 2022)
Sustainable tourism and the education that lies at its basis are related to the interpretation of UE Green Deal current heuristic curves and outcomes, which, in harmony with the 2030 Agenda, requires action and the assumption of educational co-responsibility.Pedagogy can, indeed, express an interesting cultural point of view, strengthening the interrelation between a person and their environment, between local identity and territorial branding, between the development and the quality of the involved area; this can be possible by planning a deliberate educational relationship between human and environmental development, between virtues and administrative, economic choices. Tourism, and more precisely sustainable tourism, can connect multidisciplinary interests and, at the same time, farsighted politics for the governance of society.